2019
DOI: 10.31234/osf.io/7mw5b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Annotating digital text with phonemic cues to support decoding in struggling readers

Abstract: An advantage of digital media is the flexibility to personalize the presentation of text to an individual’s needs and embed tools that support pedagogy and practice. The goal of this study was to develop a tablet-based reading tool, grounded in the principles of phonics-based instruction, and determine whether struggling readers could leverage this technology to improve their decoding skills. The tool presents a small icon below each vowel to represent its sound. Forty struggling child readers were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Initial, proof-of-concept research into Sound it Out revealed limited, yet promising effects of the cue on reading performance (Donnelly et al 2020). In a small-scale randomized controlled trial (RCT), with a short practice period (two-weeks), our research group found that the cue had a significant impact on pseudo word decoding but no significant impact on connected-text reading or real word decoding.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Initial, proof-of-concept research into Sound it Out revealed limited, yet promising effects of the cue on reading performance (Donnelly et al 2020). In a small-scale randomized controlled trial (RCT), with a short practice period (two-weeks), our research group found that the cue had a significant impact on pseudo word decoding but no significant impact on connected-text reading or real word decoding.…”
Section: Introductionmentioning
confidence: 86%
“…In order to capture a heterogeneous sample the classification of 'struggling readers' was based on performance 1 SD below the standard norm on either the Woodcock-Johnson IV Test of Achievement Basic Reading Skills (WJ BRS) or the Test of Word Reading Efficiency-2 (TOWRE Index) composite measures, and above 1 SD below the mean on the Wechsler Abbreviated Scales of Intelligence Full Scale-2 (WASI FS2) composite measure. This was the same criteria as our previous work (Donnelly et al 2020). Twenty participants had a diagnosis of developmental dyslexia.…”
Section: Methods: Study 1 Participantsmentioning
confidence: 98%
See 3 more Smart Citations